All Days 1977
DOI: 10.4043/2943-ms
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development Of Ageneral Effective Stress Method For The Prediction Of Axial Capacity For Driven Piles In Clay

Abstract: A general effective stress method for the prediction of the axial capacity of full displacement piles driven into clay is presented. The method first requires that the initial state of stress in the ground prior to pile driving be defined. The changes in stress associated with the major events in the life of a pile (pile driving, reconsolidation after driving and axial loading) are then estimated from models of pile-soil behavior and added to the initial state of stress to determine the state of stress at fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…This form of effective stress interface friction behaviour has long been advocated for the analysis of pile shaft resistance (Esrig et al, 1977;Kirby & Wroth, 1977) and is increasingly accepted as a model for piles in clay as well as sand (Bond & Jardine, 1991;Lehane et al, 1993).…”
Section: Assessment Of Axial Pipe-soil Resistancementioning
confidence: 99%
“…This form of effective stress interface friction behaviour has long been advocated for the analysis of pile shaft resistance (Esrig et al, 1977;Kirby & Wroth, 1977) and is increasingly accepted as a model for piles in clay as well as sand (Bond & Jardine, 1991;Lehane et al, 1993).…”
Section: Assessment Of Axial Pipe-soil Resistancementioning
confidence: 99%
“…4, a reduction in the size of the CS zone for k 0 < 4 results in a significant increase of viscous resistance. The minimum expected value of k 0 is about 1.4 [9,14,27]. This corresponds to a value of b 0 = 10.07 (Eq.…”
Section: Effects Of Size Of Cs Zonementioning
confidence: 94%
“…Kirby and Wroth [14] stated that the available shear strength of the soil in the CS zone will influence the side resistance of the driven shafts in clays. Other studies on the extent of the CS zone [5,9,10,14,20] using solid mechanics and experimental methods gave the range of the extent of the CS zone from 1.4 to 5 times the shaft radius from the center of the shaft. The minimum value of about 1.4 times the shaft radius is based on volume considerations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lieng et al, 2000; O' Loughlin et al, 2004;Richardson et al, 2009), although consideration must be given to the reduced strength available just after installation. Richardson et al (2009) showed that this value was approximately 6% of the long term capacity, compared with 25-45% for piles and suction caissons in normally consolidated clay (Esrig et al, 1977;Bogard and Matlock, 1990;Chen and Randolph, 2007) and that the regain in strength at the anchor interface may be quantified using a cavity expansion model.…”
Section: Figure 6 Dynamically Installed Anchor (After Araujo Et Almentioning
confidence: 96%